Radial Versus Femoral Access in Percutaneous Coronary Intervention in Acute Coronary Syndrome - Salah Uddin, Asif-Ullah, Zawar Hussain (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Although it safeguards patients from hemorrhagic disorders during cardiac procedures, the radial route is technically more challenging than the femoral approach. Aim: To evaluate the hypothesis that radial approach is the preferred strategy in ACS patients, and identifying independent predictors of the choice to choose radial access. Methods: Between August 2021 and January 2022, this prospective study was conducted in the interventional cardiology unit of Hayatabad Medical Complex Peshawar. The study included all ACS (unstable angina or myocardial infarction) patients who had previously had invasive diagnostic or therapeutic cardiac procedures. Patients who opted out of the trial were excluded. Results: Those in group 1 had a lower mean GRACE score (112±31 versus 127±40; p<0,001), improved renal function according to cretanine level (0.9±0.3 versus 1.1±1.0; p < 0.001) and a reduced prevalence of indications of left ventricular failure (6% versus 21%, p 0.003) when compared to patients in group 2. There was no difference in the groups at the time of admission for the type of ACS heart rate (69±15 Vs 75±16), systolic arterial pressure (148±31 Vs 151±33), positive troponin 59(79.7%) Vs 51(68.9%), electrocardiographic ischemia 23(31%) Vs 19(25.7%), three-vessel disease (30, 40.5%) VS 25(33.8%) Practical implication: The variables that determined the preference for radial approach reflect the clinical status and severity of the patients, demonstrating that the convenience of the approach is more valued in extremely complex patients than its antihemorrhagic effectiveness. Conclusion: The trend for radial access to be preferred over femoral access during coronary intervention was not primarily influenced by the patient population’s risk of bleeding. Keywords: Angioplasty, Coronary Artery Disease, Radial Artery, Femoral Artery.